Enhanced performance of a flexible and wearable piezoelectric nanogenerator using semi-insulating GaN:Mg/ZnO coaxial nanowires. (December 2021) - Waseem, Aadil; Johar, Muhammad Ali; Abdullah, Ameer; Bagal, Indrajit V.; Ha, Jun-Seok; Lee, June Key; Ryu, Sang-Wan
Abstract: Flexible piezoelectric nanogenerators (PNGs) with high power-conversion efficiency are of great interest. Here, we propose wearable PNGs based on pristine magnesium (Mg)-doped GaN (GaN:Mg) and GaN:Mg/ZnO coaxial nanowires (NWs) exhibiting state-of-the-art high-voltage and -current outputs. The PNGs were designed to suppress internal screening by a reduction in the diameter of the NWs, successful incorporation of Mg in GaN NWs as a p-type dopant, and deposition of a ZnO shell on the GaN:Mg NWs. The Fermi-level pinning reduces free carriers in thin NWs (diameter up to ~30 nm). By tuning the size of the metal–alloy catalyst, we obtained NWs with diameters ranging from 30 to 50 nm. To deplete the NWs fully of free carriers, Mg is incorporated without activation, which enhanced the resistance of GaN:Mg NWs by forming inactive Mg–H complexes. The flexible PNG fabricated with pristine GaN:Mg NWs exhibited the maximum output voltage and current of 52 V and 23 µA, respectively. The junction current screening was suppressed by depositing a ZnO shell with an optimized thickness of 10 nm on GaN:Mg NWs. The PNG fabricated with GaN:Mg/ZnO coaxial NWs showed an enhanced output voltage and current of 66 V and 40 µA and demonstrated a state-of-the-art high power density of 170 µW/cm 2 at an optimum load resistance of 2.5 MΩ. When mounted on the wrist as a wearable healthcare monitoring device, it successfully detected the movement of tendons and muscles as soon as the fingers were moved and exhibited a corresponding change in voltage response. Additionally, the charging of a capacitor is proven by the PNG under continuous foot tapping, demonstrating its potential to charge energy storage devices by walking or jogging. Graphical Abstract: ga1 Highlights: GaN:Mg/ZnO coaxial NWs exhibits state-of-the-art high power density of 170 µW/cm 2 . Semi-insulating GaN:Mg NWs exhibited the highest output voltage of 52 V. The p-n heterojunction atop of GaN:Mg/ZnO coaxial NWs enhanced the output voltage to 66 V. The PNG exhibited high sensitivity by measuring slight movement of tendons of wrist. It also demonstrated the charging of a capacitor under continuous foot taping.